Nutritional Status, Physical Activity, Family History of Hypertension, and Dietary Patterns as Risk Factors for Hypertension Among Individuals Aged 20–59 Years - I Made Rai Sudarsono; Nurhafifah Hamsa; Hasan; Imanuddin; Hariani (Jurnal Penelitian Pendidikan IPA, 2025)
Hypertension is an increasing global health concern and a leading cause of cardiovascular diseases, including stroke and heart attack. In Indonesia, the prevalence of hypertension continues to rise each year, including in the service area of Puskesmas Perumnas, Kendari City. This study aims to examine the factors associated with hypertension in individuals aged 20–59 years, specifically from the perspectives of nutritional status, physical activity, family history of hypertension, and dietary patterns. This research is an analytical observational study using a case-control design. It was conducted from February to March 2025 in the service area of Puskesmas Perumnas. A total of 98 participants were involved, consisting of 49 hypertensive individuals (cases) and 49 non-hypertensive individuals (controls), selected using purposive sampling. Data was collected through questionnaires and direct measurements, then analyzed using odds ratio and chi-square tests. Cases and controls in this study were comparable in age and gender. Variables that showed a significant association and were proven to be risk factors for hypertension were overweight status (OR = 2.73; 95% CI = 1.20–6.18; p = 0.03), family history of hypertension (OR = 2.72; 95% CI = 1.20–6.16; p = 0.03), and adequate/unhealthy dietary patterns (OR = 6.28; 95% CI = 2.61–15.11; p = 0.00). These three variables contributed to a significant increase in the risk of hypertension. In contrast, light physical activity (OR = 1.51; 95% CI = 0.68–3.36; p = 0.42) did not show a significant association with hypertension and was therefore not considered a risk factor in this study. Overnutrition, a family history of hypertension, and an adequate/unhealthy diet are significant risk factors for hypertension in adulthood, while light physical activity has not been shown to be a significant risk factor. Hypertension prevention efforts should focus on weight control, dietary modification, and screening for individuals with a family history of hypertension.